Profile of Peripartum Cardiomyopathy Patients at Waled Re-gional Hospital, Cirebon Regency, January 2022 - June 2025 - Laela Susilawati; Rini Istisakinah; Nunung Nurbaniwati (International Journal of Health and Pharmaceutical (IJHP), 2026)
Peripartum cardiomyopathy (PPCM) is an important cause of heart failure during pregnancy and postpartum, but patient profile data at district hospitals such as Waled Regional Hospital, Cirebon is still very limited. This study aims to describe the profile of peripartum cardiomyopathy patients at Waled Regional Hospital, Cirebon Regency, from January 2022 to June 2025. A retrospective descriptive study design was used with secondary data analysis from the medical records of all patients diagnosed with PPCM, including variables such as age, hypertension, diabetes mellitus, parity, multiple pregnancies, hemoglobin levels, random blood sugar, urea, creatinine, and echocardiography results (LVEF). Analysis was performed with univariate frequency distribution using nominal and ordinal scales. The results showed that most patients were aged 36–45 years (45.16%), multiparous (54.84%), had grade II hypertension (39.03%), and had LVEF <40% (77.42%), while diabetes mellitus and multiple pregnancies were very rare. Thus, in this setting PPCM primarily affects elderly multiparous mothers with severe hypertension and left ventricular systolic dysfunction, highlighting the need for strengthened risk-based screening and collaborative management between obstetrics and cardiology